Food in zones of conflict : cross-disciplinary perspectives - Collinson, Paul, 1969-; Macbeth, Helen M. (Anthropology of food and nutrition, 2014)
The availability of food is an especially significant issue in zones of conflict because conflict nearly always impinges on the production and the distribution of food, and causes increased competition for food, land and resources. Controlling the production of and access to food can also be used as a weapon by protagonists in conflict. The logistics of supply of food to military personnel operating in conflict zones is another important issue. These themes unite this collection, the chapters of which span different geographic areas. This volume will appeal to scholars in a number of different disciplines, including anthropology, nutrition, political science, development studies and international relations, as well as practitioners working in the private and public sectors, who are currently concerned with food-related issues in the field.